2009
DOI: 10.1074/jbc.m109.026435
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and Characterization of the Heterodimerization of ZnT5 and ZnT6 in the Early Secretory Pathway

Abstract: The majority of CDF/ZnT zinc transporters form homooligomers. However, ZnT5, ZnT6, and their orthologues form hetero-oligomers in the early secretory pathway where they load zinc onto zinc-requiring enzymes and maintain secretory pathway functions. The details of this hetero-oligomerization remain to be elucidated, and much more is known about homo-oligomerization that occurs in other CDF/ZnT family proteins. Here, we addressed this issue using co-immunoprecipitation experiments, mutagenesis, and chimera studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 39 publications
3
104
2
Order By: Relevance
“…Immunofluorescence-Immunostaining for FLAG-hZnT1, hZnT2-HA, hZnT3-Myc, hZnT4-HA, or mZnT8-HA expressed in TKO cells was performed as described previously (20). Briefly, the cells were stained with anti-HA antibody (1:50; Sigma) for hZnT4-HA, with anti-HA tag antibody (1:100; MBL, Nagoya, Japan) for hZnT2-HA and mZnT8-HA, with anti-Myc tag antibody (1:100; MBL) for hZnT3-Myc, or with anti-FLAG tag antibody (anti-DDDDK; 1:100; MBL) for FLAG-hZnT1, followed by Alexa 488-conjugated goat anti-rabbit IgG (1:250; Molecular Probes, Eugene, OR), or with anti-GM130 antibody (1:100; BD Transduction Laboratories), followed by Alexa 594-conjugated goat anti-mouse IgG (1:250; Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence-Immunostaining for FLAG-hZnT1, hZnT2-HA, hZnT3-Myc, hZnT4-HA, or mZnT8-HA expressed in TKO cells was performed as described previously (20). Briefly, the cells were stained with anti-HA antibody (1:50; Sigma) for hZnT4-HA, with anti-HA tag antibody (1:100; MBL, Nagoya, Japan) for hZnT2-HA and mZnT8-HA, with anti-Myc tag antibody (1:100; MBL) for hZnT3-Myc, or with anti-FLAG tag antibody (anti-DDDDK; 1:100; MBL) for FLAG-hZnT1, followed by Alexa 488-conjugated goat anti-rabbit IgG (1:250; Molecular Probes, Eugene, OR), or with anti-GM130 antibody (1:100; BD Transduction Laboratories), followed by Alexa 594-conjugated goat anti-mouse IgG (1:250; Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…There is, however, almost no information about the activation step of these enzymes in the secretory process. Using a gene disruption/reexpression system in chicken DT40 cells, and ALPs as marker proteins, we have shown that two ZnT complexes (ZnT5/ZnT6 heterodimers and ZnT7 homo-oligomers) activate zinc-requiring enzymes that have matured during the secretory process, converting them from the apo-to the holo-form (7,8,19,20). We used both placenta ALP and tissue nonspecific ALP (TNAP) because their activities are wholly dependent on zinc.…”
mentioning
confidence: 99%
“…ZnT6 mRNA was detected in the islets of Langerhans [34], its functional heterodimerization with ZnT5 has been described [35], and its presence in purified β cells from both mouse [36] and human [37,38] confirmed by massive parallel sequencing (RNASeq).…”
Section: Znt Familymentioning
confidence: 96%
“…2D). Moreover, based on the high evolutionary conservation (data not shown) along with the putative homodimer model interface (formed by superimposing the one modeled monomer onto one interacting YiiP monomer), ZnT-2 is likely to form a homodimer that is similar to multiple zinc transporters that have been shown to form homodimeric or heterodimeric structures including ZnT-3, ZnT-5, ZnT-6, and ZnT-8 (42,44,45).…”
Section: Znt-2 Mutations and Neonatal Zinc Deficiencymentioning
confidence: 99%
“…First, the zinc transporters ZnT-3, ZnT-4, and ZnT-8 which are close homologues of ZnT-2, form homodimers or heterodimers (42,44,45). Second, there is high evolutionary conservation along the putative interface of the homodimeric ZnT-2 model, which was created based on the crystal structure of the E. coli homodimeric zinc transporter YiiP.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%